2020
DOI: 10.1186/s41938-020-0209-6
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus velezensis BM21, a potential and efficient biocontrol agent in control of corn stalk rot caused by Fusarium graminearum

Abstract: The present work was conducted to screen and identify biocontrol bacteria that effectively reduce the severity of corn stalk rot (CSR) and clarify the antifungal activity of secondary metabolites. The bacterial strain (BM21) was isolated from corn rhizosphere soil that effectively reduced CSR in pot experiments. On the basis of phylogenetic reconstructions, 16S rRNA sequence analysis, and biochemical and physiological reactions, BM21 was identified as Bacillus velezensis. The strain exhibited remarkable antifu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
24
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 27 publications
5
24
0
4
Order By: Relevance
“…Similar findings were observed that Bacillus velezensis, the strain exhibited remarkable antifungal activity against Fusarium graminearum, a pathogenic fungus that causes Corn Stalk Rot [12] and Bacillus subtilis BR23 strain controlled BLSB, when applied as Seed Treatment and Soil Application on corn crop [17]. As per the findings of McMullen and Lamey [18], B.subtilis used as seed treatment colonize the developing root system, suppressing disease organisms such as Fusarium and Rhizoctonia.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Similar findings were observed that Bacillus velezensis, the strain exhibited remarkable antifungal activity against Fusarium graminearum, a pathogenic fungus that causes Corn Stalk Rot [12] and Bacillus subtilis BR23 strain controlled BLSB, when applied as Seed Treatment and Soil Application on corn crop [17]. As per the findings of McMullen and Lamey [18], B.subtilis used as seed treatment colonize the developing root system, suppressing disease organisms such as Fusarium and Rhizoctonia.…”
Section: Discussionsupporting
confidence: 80%
“…Trichoderma harzianum, showed 68% of inhibition of the mycelia of R. solani, under in vitro conditions [11]. Bacterial strains from the corn rhizosphere soil were isolated and screened in vitro for antagonistic activity against F. graminearum [12]. Among biocontrol microbes, Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Other Bacillus isolates, such as B. subtilis , B. amyloliquefaciens , and B. velezensis had been found to inhibit spore morphology or mycelial growth of F. graminearum ( Zhao et al, 2015 ; Jamal et al, 2017 ; Lee et al, 2017 ; Chen et al, 2018 ; Wang et al, 2020 ). Abnormally swollen spores and hyphae of plant pathogens were previously reported in dual cultures with endophytic bacteria ( Lee et al, 2017 ; Saechow et al, 2018 ; He et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Antagonistic activity against the pathogens Monilinia fructicola [ 61 ] and B. cinerea (60%) reached maximum levels of > 80% and 60%, respectively, mainly due to the large amount of lipopeptides produced (10 g/L) [ 67 ]. Many studies of olive, tomato, corn, peanut, pepper, maize and rice crop yields have also described the biocontrol activity of B. velezensis strains against phytopathogens such as Verticillium dahliae , Fusarium graminerarum , Sclerotium rolfsii , Phytophthora and B. cinerea [ 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. Our results are in line with the findings of Lee et al (2006) [ 75 ] who investigated the effect of radicular applications of B. subtilis WXCDD105 on B. cinerea in tomato plants.…”
Section: Discussionmentioning
confidence: 99%